2017
DOI: 10.1186/s12977-017-0328-7
|View full text |Cite
|
Sign up to set email alerts
|

HIV signaling through CD4 and CCR5 activates Rho family GTPases that are required for optimal infection of primary CD4+ T cells

Abstract: BackgroundHIV-1 hijacks host cell machinery to ensure successful replication, including cytoskeletal components for intracellular trafficking, nucleoproteins for pre-integration complex import, and the ESCRT pathway for assembly and budding. It is widely appreciated that cellular post-translational modifications (PTMs) regulate protein activity within cells; however, little is known about how PTMs influence HIV replication. Previously, we reported that blocking deacetylation of tubulin using histone deacetylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 58 publications
(75 reference statements)
2
21
0
Order By: Relevance
“…We analyzed phosphopeptides with large fold-changes at both the 1- and 15-min time points and found nearly all were from proteins with roles in either (1) actin cytoskeletal architecture, endocytosis, and movement of vesicles along actin and tubulin networks, or (2) transcription, mRNA splicing and capping, translation, or acetylation of methionine residues on newly produced proteins. These data support previous studies demonstrating that these pathways are actively modulated by signaling upon HIV binding to the cell surface [ 22 , 26 , 27 , 30 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We analyzed phosphopeptides with large fold-changes at both the 1- and 15-min time points and found nearly all were from proteins with roles in either (1) actin cytoskeletal architecture, endocytosis, and movement of vesicles along actin and tubulin networks, or (2) transcription, mRNA splicing and capping, translation, or acetylation of methionine residues on newly produced proteins. These data support previous studies demonstrating that these pathways are actively modulated by signaling upon HIV binding to the cell surface [ 22 , 26 , 27 , 30 ].…”
Section: Resultssupporting
confidence: 92%
“…Rho GTPases regulate a variety of cellular processes including cytoskeletal dynamics, transcription, endosomal trafficking, cell cycle, cell adhesion and cytokinesis. The observation that HIV signaling influences Rho GTPase signaling pathways has been explored by our lab recently, in combination with a small molecule screen that implicated Rho GTPases in regulation of HIV infection [ 30 ]. Briefly, CCR5-tropic signaling was found to dramatically alter the cellular Rho GTPase landscape, regulating not only cdc42 and Rac1 GTPases but also at least 25 guanosine dissociation inhibitors (GDIs), guanosine exchange factors (GEFs) and GTPase activating proteins (GAPs) that influence GTPase signaling.…”
Section: Resultsmentioning
confidence: 99%
“…We observed a pronounced upregulation response at the RNA level, for the most part involving signal transduction pathways, as opposed to the other two omics levels. Our data suggest that HIV-1 influences the signaling mechanisms of infected cells mainly by affecting expression of cell surface receptors, chemokine receptors, G-protein-coupled receptors, or genes involved in signaling of Rho GTPases (Supplementary File S5), recapitulating previous findings 2225 . At the protein and phosphoprotein levels, the identified differentially expressed genes were mainly enriched in pathways describing immune system, metabolism, gene expression, cell cycle, and HIV-related processes (Fig.…”
Section: Resultssupporting
confidence: 87%
“…The authors conclude that the Cdc42-NWASP-Arp2/3 pathway may be equal to or more important than the Rac1 pathway described above [ 137 ]. Recent studies have confirmed this hypothesis, by showing that Env signaling through CD4 and CCR5 leads to activation of both Rac1 and Cdc42 in primary CD4 T-cells ( Figure 2 a) [ 138 ]. Similarly, ingenuity pathway analysis scored Cdc42 and Rac1 pathways within the top-five deregulated cellular networks in T-cells that are exposed to cell-free [ 138 ], or cell-transmitted virus [ 139 ].…”
Section: Manipulation Of the Actin Cytoskeletonmentioning
confidence: 76%